The role of lactylation in tumor growth and cancer progression - Al-Malsi, Khulood; Xie, Sinan; Cai, Yunshi; Mohammed, Nader; Xie, Kunlin; Lan, Tian; Wu, Hong (Frontiers in Oncology, 2025)
BackgroundLactate’s perception of lactate has changed over the last 30 years from a straightforward metabolic byproduct to a complex chemical with important biological activities, such as signal transduction, gluconeogenesis, and mitochondrial respiration. In addition to its metabolic contributions, lactate has far-reaching repercussions. This review highlights the role of lactate in the course of cancer by highlighting lactylation as a unique epigenetic alteration. The purpose of this review is to clarify the functions of lactate in the biology of tumors, with a particular focus on the translational potential of lactylation pathways in cancer diagnosis and treatment approaches.MethodsThis review summarizes research on the relationship between lactate and cancer, with an emphasis on histone lactylation, its effect on gene expression, and its influence on the tumor microenvironment. By establishing a connection between metabolic byproducts and epigenetic gene regulation, we investigated how lactylation affects immune regulation, inflammation, and cellular repair.FindingsHistone lactylation, or the addition of lactate to lysine residues on histone proteins, increases transcriptional activity and facilitates the expression of genes involved in homeostasis and repair. These findings have important implications for cancer treatment. Lactylation, for example, activates genes such as Arg1, which is a hallmark of the M2 macrophage phenotype implicated in immunosuppression and tumor growth. The ability of lactate to dynamically alter gene expression is further supported by its function as a histone deacetylase(HDAC)inhibitor and its impact on histone acetylation. Its wide-ranging involvement in cellular metabolism and epigenetic control has been demonstrated by the discovery of particular lactylation sites on histones in various cell types, including cancer cells.